Analysis Of Indonesian Tourism Potential and its Impact on Gross National Product (GNP) - Sanga, Ferdinandus Masan; Gunawan , Cakti Indra (International Research & Development for Human Beings (IRDH), 2024)
This study aims to describe the potentials of Indonesian tourism, the impacts of tourism on local communities around tourism and the impact on the country of Indonesia as well as the impact of tourism on Gross National Product (GNP). The method used in this study uses descriptive analysis, namely the literature comparison method and the triangulation method. The results of this study indicate that the tourism sector contributes significantly to the country, the community around tourism, and Gross National Product (GNP), especially foreign exchange earnings, creating jobs, and foreign investment. Leading destinations such as Lombok, Bali, Manado, Labuan Bajo, and other tourism areas show consistent growth in contribution, although there are challenges in the form of inequality in infrastructure development and service quality in several tourist areas.